Early and delayed effect of 2% chlorhexidine on the shear bond strength of composite restorative material to dentin using a total etch adhesive - Khalil, Rabeia J; Al-Shamma, Abdulla M (Journal of Baghdad College of Dentistry, 2015)
Background: Lack of durability of the bond of the dental adhesive systems to tooth structure is one of the most important problems in tooth colored restorative work. This in vitro study was performed to evaluate the effect of 2% chlorhexidine gluconate(CHX) on dentin bond strength by using total etch adhesive system at twenty-four hours and three months of water storage.Material and methods:A flat dentin surface was prepared for forty sound human maxillary premolar teeth which were acid etched with 36% phosphoric acid gel after being divided randomly into four groups of ten teeth each according to storage time and CHX application, theCHX was applied for 60 seconds before adhesive application for groups I and III which were tested after twenty-four hours and three months respectively, while the distal water was applied for 60 seconds before the application of adhesive for group II and IV which were tested after twenty-four hours and three months respectively.The Prime and BondÂ® NTâ„¢ adhesive (Dentsply) was applied and cured, Composite (Ceram X mono, Dentisply) was applied through special mold with 2 mm thickness and light cured, Then all specimens were stored in distilled water 37oC until the time of testing of each group.Shear bond strength test was performed at the end of the storage period (24 hours or 3 months).Results:T-test results showed high statistically significant reduction in shear bond strength (SBS) in non CHX group IV (tested after 3 months) compared to non CHX group II (tested after 24 hours)(P< 0.01). In CHX groups I (tested after 24 hours) and III (tested after 3 months), results showed no statistically significant differences in shear bond strength(p> 0.05).On the other hand result showed statistically no significant differences between groups I and II in 24 hours shear bond strength (P> 0.05). After 3 months water storage, there was statistically high significant differences between the groups III and IV (P< 0.01).Conclusion: the use of 2 % CHX glocounate solution after acid etching and before bonding of dentin have no adverse effect on immediate bond strength (24 hours storage), and was effective in reducing degradation of resin-dentin bond interface after three months of water storage.